STARTING THE VIOLIN TRAINING - AYDIN, Birol (SSD Journal, 2022)
The purpose of this study is to make a training guide book by emphasizing the importance of the basic technical hardware of the violin and the importance of the start-up phase. The reason why the focus is especially on the start-up phase is that certain obstacles and mistakes occurring in the advanced stages are the ones which have been ignored, learned and/or taught during this phase. In this study, playing techniques in parallel with the physical changes of the violin from the past to today are mentioned and the study has been corroborated with the images in order to be comprehensive about the development process of being the violin performer. Since violin training is a type of master-apprentice relationship, by making use of the experiences of important violinists and violin masters, a lot of elements have been included in this study to raise awareness of both the teacher and the student. Holding and posture experiences in the study have been exemplified so as to provide the most physically-comfortable way of playing based on modern violin playing techniques. The important steps in violin training such as the adaptation of the student to the instrument, the relationship of the teacher and the student, first sessions, holding, posture and the experience of the first concert have been explained in detail. The data, obtained by the literatüre review, has been evaluated qualitatively and synthesized with the personal experiences of the auther, who is also a vioin educator. The study is considered important in terms of its usage in the violin training curriculum.